EDUKASI PERILAKU BERINTEGRITAS PADA SANTRI PONDOK PESANTREN DARUTTAUBAH - Bangun, Mic Finanto Ario; Syauket, Amalia (LPPM Universitas Flores, 2024)
Integrity means strength, wholeness, completeness, and invulnerability. Integrity behaviour refers to the unity of self and moral honesty. Integrity shows consistency between words and actions in daily life. A person with integrity usually thinks before speaking so that their behaviour and actions align with what is said. Santri is a term for someone who learns or seeks Islamic religious knowledge at a pesantren (Islamic boarding school) in Indonesia. Santri usually lives at the pesantren to follow an educational process involving the teaching of spiritual knowledge. The community service program with the theme